Políticas y estrategias de la crítica : ideología, historia y actores de los estudios literarios - Ugalde, Sergio, 1977-; Ette, Ottmar (Bibliotheca Ibero-Americana, 2016)
The articles in this volume analyze the ideological dimensions of literary studies (their polemics and projects) in that they examine specific figures (philologians, historians of literature, essayists) and put forth contemporary conceptualizations about the literary and cultural phenomenon.